Periodontal Therapy as an Adjunct to Pulmonary Rehabilitation in Chronic Respiratory Diseases: A Randomized Controlled Trial - Anuj S. Parihar; Neha Khare; Sneha Bayyapu; Maninderjit Kaur; Deepak Kochar; Rashmi Laddha (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic respiratory diseases (CRDs) significantly impact quality of life and are linked to systemic inflammation. This study explores the potential connection between oral and respiratory health by investigating the benefits of integrating periodontal therapy into pulmonary rehabilitation (PR) for CRD patients. Objective: This randomized controlled trial (RCT) assessed the impact of periodontal therapy combined with PR on lung function, quality of life, and systemic inflammation in CRD patients. Methods: 2500 adults with CRDs and moderate to severe periodontal disease were randomized to receive standard PR or PR plus periodontal therapy. The primary outcome was the change in forced expiratory volume in one second (FEV1). Secondary outcomes included quality of life, inflammatory markers, and periodontal health parameters. Results: The combined therapy group showed significantly greater improvements in FEV1 (P < 0.001), quality of life (P < 0.05), and inflammatory markers (P < 0.01) compared to the PR-only group. Significant improvements were also observed in all periodontal health parameters in the combined therapy group. Conclusion: Integrating periodontal therapy into PR programs provides additional benefits for CRD patients, suggesting a potential mechanism through which addressing periodontal inflammation positively impacts overall health. These findings support the inclusion of periodontal therapy as an adjunctive treatment strategy in CRD management.